2012
DOI: 10.1016/j.anr.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of High Blood Pressure and its Relationship with Body Weight Factors among Inpatients with Schizophrenia in Taiwan

Abstract: The findings of this research shed light on the importance of developing effective weight and blood pressure monitoring and management programs for inpatients with schizophrenia. There is also a need for clinical nurses to employ multiple behavioral intervention strategies to minimize risks of high BP in patients with schizophrenia. We recommend that clinical nurses carefully monitor and control BP among inpatients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…This is reflected in our logistic regression analysis because factors in our sample could account for low variance. Our findings on the prevalence of HTN are lower than those of a study done in Taiwan, 15 which had mostly inpatients who were more severely ill. But obesity and SGA use are similar to the findings of the Taiwan study.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…This is reflected in our logistic regression analysis because factors in our sample could account for low variance. Our findings on the prevalence of HTN are lower than those of a study done in Taiwan, 15 which had mostly inpatients who were more severely ill. But obesity and SGA use are similar to the findings of the Taiwan study.…”
Section: Discussioncontrasting
confidence: 95%
“…Newer studies done after the introduction of SGAs have found HTN to be more prevalent among inpatients with schizophrenia than the general population in Taiwan, and HTN was significantly associated with a higher BMI. 15 HTN without any other cardiometabolic comorbidity is found to have more accelerated cardiac effects than the age-matched general population. 16 The prevalence of cardiovascular diseases and their risk factors has increased worldwide, and similarly for persons with schizophrenia.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, it is also reported that the increase in BP could also be partly linked to increases in body weight and BMI in psychotic patients. 41 The increase in BP by AAPs is mediated via the dopaminergic system through D1, D3, and D4 receptors which are hypothesized to interact with the renin–angiotensin–aldosterone system. Furthermore, it is suggested that dopaminergic receptors, D2 and D5, when activated, also inhibit the production of norepinephrine consequently leading to the increase in BP.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The excess mortality and morbidity in schizophrenia is largely attributed to comorbidities such as diabetes mellitus (DM), cardiovascular diseases (CVD), hypertension (HTN), obesity, and dyslipidemia. [123]…”
Section: Introductionmentioning
confidence: 99%